Pelatihan dan Pendampingan Pembuatan Bahan Ajar Digital dengan Pendekatan Multiple Representations berbantuan Artificial Intelligence (AI) bagi Guru SMA Negeri 4 Takalar - Ardiana, Ardiana; Nurazmi, Nurazmi; Nurfadilah, Nurfadilah (Jurnal SOLMA, 2025)
Background: The availability and quality of learning materials directly impact the effectiveness of teaching. At SMA Negeri 4 Takalar, the majority of teachers (90%) rely on printed textbooks, which are limited in number, thus hindering students' access to learning resources. This community service program aims to enhance teachers' ability to design digital learning materials rich in multiple representations (text, images, audio, video, interactive quizzes) with the support of AI-based applications. Methods: The method employed involves in-house training and direct mentoring on the use of AI in creating digital learning materials, utilizing applications such as Prezi, ChatGPT, Canva, Invideo, and Book Creator. Results: The results showed a significant improvement in teachers' understanding of the multiple representations approach, which enriches learning materials with various multimodal elements. Additionally, teachers gained skills in creating AI-assisted digital learning materials, enabling them to independently produce interactive content. More than 80% of teachers have applied more diverse representations in their teaching modules, including text, images, audio, and videos. Conclusions: This program successfully improved teachers' ability to create digital learning materials for use in their respective classrooms.